Research on Financial Accounting of GDP Index Based on Numerical Simulation - Bo Li (Advances in Multimedia)
Because the traditional GDP accounting method was difficult to meet the actual needs of governments for economic and social development, aiming at the problems of unclear data sources related to GDP and inconsistent GDP accounting results in the national economic accounting system, a GDP index financial accounting method based on numerical simulation was proposed. Firstly, it summarized the traditional GDP thought and its related accounting methods and analyzed the common problems existing in the traditional GDP accounting. Secondly, it expounded the concept of green GDP and its accounting scope and theoretical model and pointed out the key problems to be solved in green GDP accounting, such as ecological resource consumption and environmental pollution cost calculation. Finally, by analyzing the relationship between green GDP and main supporting indicators, the accounting method of GDP indicators based on numerical simulation was proposed, and the accounting result detection model based on the econometric model was given. Through empirical analysis, it showed that the GDP accounting method proposed in this paper has good feasibility and effectiveness and can effectively reflect the development of the economic operation. The accounting method proposed in this paper can also provide a reference basis for the construction of a green GDP system.